2019
DOI: 10.1002/hon.2607
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular mortality among patients with non‐Hodgkin lymphoma: Differences according to lymphoma subtype

Abstract: Survival rates of patients with non‐Hodgkin lymphoma (NHL) have improved over the last decade. However, cardiotoxicities remain important adverse consequences of treatment with chemotherapy and radiation, although the burden of cardiovascular mortality (CVM) in such patients remains unknown. We conducted a retrospective cohort study of patients greater than or equal to 20 years of age diagnosed with diffuse large B‐cell lymphoma (DLBCL), follicular lymphoma (FL), and chronic lymphocytic leukemia/small lymphocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 35 publications
1
9
0
Order By: Relevance
“…Notably, multivariate analysis indicated that radiotherapy reduced CVD-specific mortality in patients with thyroid cancer. This finding seems to contrast with the known cardiotoxic effect of EBRT but is line with results from some previous studies reporting reduced risk or no excess risk of CVD death associated with EBRT [27][28][29][30]. A possible explanation is that patients who undergo radiotherapy receive more preventive cardiology care.…”
Section: Discussionsupporting
confidence: 89%
“…Notably, multivariate analysis indicated that radiotherapy reduced CVD-specific mortality in patients with thyroid cancer. This finding seems to contrast with the known cardiotoxic effect of EBRT but is line with results from some previous studies reporting reduced risk or no excess risk of CVD death associated with EBRT [27][28][29][30]. A possible explanation is that patients who undergo radiotherapy receive more preventive cardiology care.…”
Section: Discussionsupporting
confidence: 89%
“…However, we hold the opinion that reducing or strengthening the intensity of chemotherapy is extreme. In clinical treatment, it is still necessary to comprehensively assess the possibility of cardiovascular death in patients by using age, staging, sex, and other factors to develop individualized chemotherapy schemes 20 …”
Section: Discussionmentioning
confidence: 99%
“…In contrast to infections, cardiovascular and neurological diseases – the other most common non‐cancer deaths in patients with LPL/WM (Castillo et al , ) – posed no overall increased risk of mortality compared to the general population. The borderline but not significantly elevated mortality risk (SMR 1·1) from cardiovascular diseases after LPL/WM contrasts with strikingly increased cardiovascular mortality risks among patients with other NHLs and solid cancers (Abuamsha et al , ; Sturgeon et al , ), possibly reflecting lower use of cardiotoxic agents and radiotherapy in LPL/WM. Decreased risks of neurological deaths may be due to under‐reporting of dementia as an underlying cause of death (Macera et al , ; Ganguli & Rodriguez, ; Ives et al , ; Romero et al , ), although the novel finding of elevated risk of death due to cerebrovascular diseases exclusively in patients aged <65 years at LPL/WM diagnosis correlates with the higher observed rates of symptomatic hyperviscosity among younger patients with WM (Bustoros et al , ).…”
Section: Discussionmentioning
confidence: 99%